The first equation is
![y-2x+1=0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/b1kaoove07eu81wpq4y36rrqizs09olp4u.png)
(Equation 1)
The second equation is
(Equation 2)
Putting the value of x from equation 1 in equation 2.
we get,
![4x^(2)+3(2x-1)^(2)-2x(2x-1)=7](https://img.qammunity.org/2019/formulas/mathematics/middle-school/4qh1ovddz42e7h6641dwslqc0grvscapuw.png)
![4x^(2)+3(4x^(2)+1-4x)-4x^(2)+2x=7](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ca2quc2nmnc5fdu7p8eu06cb4eaa6kq1wm.png)
by simplifying the given equation,
![12x^(2)-10x-4=0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/a5msx8thp1j0m9h1thh3x9hoob7kne25aw.png)
![6x^(2)-5x-2=0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ac3ruulcwha65lnfd88pklsgznwaaoxlv7.png)
Using discriminant formula,
![D=b^(2)-4ac](https://img.qammunity.org/2019/formulas/mathematics/middle-school/rq82uhvu3xwznckb6k6d5x9w5u43bgy381.png)
![D=25-4 * 6 * -2 = 73](https://img.qammunity.org/2019/formulas/mathematics/middle-school/mp24u7jit5qj5pn8glr0jgdalsmenchw6t.png)
Now the formula for solution 'x' of quadratic equation is given by:
![x=(-b+√(D))/(2a) and x=(-b-√(D))/(2a)](https://img.qammunity.org/2019/formulas/mathematics/high-school/68htne4b52z1m0v1nziroa8cpvw0xvfbqq.png)
![x=(5+√(73))/(12) and x=(5-√(73))/(12)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/fk1gvcbq0fdiw4p75e74xslytbe4uvbmxo.png)
Hence, these are the required solutions.